A composite getter material with high efficiency in absorbing nitrogen and a preparation method thereof
By introducing Zr-Ti-V metal compound into the getter material, the composite getter material is solved, and the problem of low efficiency of the existing getter material when absorbing N2 is solved, and the efficient absorption capacity of CO, H2O and N2 is achieved.
Patent Information
- Application Number
- CN202411327550.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-09-23
AI Technical Summary
Existing getter materials are not efficient when absorbing non-polar N2 molecules, and cannot effectively solve the problem of N2 absorption in diversified gas environments.
A composite getter material is used, including main component A and additive component B. The main component A is a nano-formed (SiO2)1-x-y-z(Al2O3)x(CaO)yCz material, and additive component B is a Zr-Ti-V metal compound. A AAbB composite getter is formed through physical mixing to improve the absorption capacity of N2.
The absorption capacity of getter materials to CO, H2O and N2 is significantly improved, and the problem of low efficiency of traditional getter materials when absorbing N2 is solved, which enhances the processing capacity of diversified gas environments.
Smart Images

Figure CN119158542B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of new materials, and in particular to a composite getter material capable of efficiently absorbing nitrogen and a preparation method thereof. Background Art
[0002] In modern industry, scientific research and daily life, efficient and stable getter materials are essential for maintaining gas purity and low-pressure environment in closed systems (such as vacuum equipment, gas storage containers, electronic device packaging, etc.). Traditional metal oxide getter materials are widely used for their good absorption performance for specific gases (such as CO and H2O). However, when facing inert gases such as N2, these materials often show the limitation of insufficient absorption capacity, which limits their application effect in occasions where multiple gas components need to be controlled simultaneously.
[0003] Existing getter materials, because of their abundant active sites on their surfaces, can effectively adsorb and fix polar molecules such as CO and H2O, for example, metal oxides (SiO2) 1-x-y-z (Al2O3) x (CaO) y C z Getter material is a mixture of metal oxides SiO2, Al2O3, CaO and activated carbon powder in a certain proportion, which makes it capable of effectively absorbing CO and H2O. It can be used in impure gases containing CO and H2O or in a vacuum environment to effectively remove impurities in the gas, thereby achieving the effect of purifying the gas or removing CO and H2O in a vacuum environment.
[0004] However, for non-polar N2 molecules, the adsorption efficiency of metal oxides is significantly reduced due to the lack of effective interaction mechanism. 1-x-y-z (Al2O3) x (CaO) y C z Getters are widely used and can effectively remove impurities such as H2O or CO in gases. However, the impurities in gases are generally diversified, such as N2. If N2 is to be absorbed, the current (SiO2) 1-x-y-z (Al2O3) x (CaO) y C z Getters won't solve this problem. Summary of the invention
[0005] The main object of the present invention is to solve the technical problem of low adsorption efficiency of non-polar N2 molecules in the prior art. A composite getter material with high nitrogen absorption efficiency, the composite getter material includes a main component A and an additive component B, the main component A and the additive component B form a aAbB composite getter, where a + b = 100%; 50wt% ≤ a < 100wt%; 0wt% < b < 50wt%; the components of the main component A are: (SiO2) 1-x-y-z (Al2O3) x (CaO) y C z , where 20wt% ≤ x ≤ 70wt%; 10wt% ≤ y ≤ 60wt%; 0wt% ≤ z ≤ 40wt%; the additive component B is a metal compound Zr-Ti-V getter material.
[0006] The main component A is a powder with a particle size of 3 - 5nm. The additive component B is a powder with a particle size of 8 - 50 microns. In the aAbB composite getter, 60wt% ≤ a ≤ 95wt%; 1wt% ≤ b ≤ 40wt%.
[0007] The second aspect of the present invention provides a preparation method of a composite getter material with high nitrogen absorption efficiency, including the following steps:
[0008] SiO2, Al2O3, CaO, activated carbon C powders with different contents and a powder particle size composition of 70 - 230μm are put into a ball mill of model XXX according to the composition ratio of (SiO2) 1-x-y-z (Al2O3) x (CaO) y C z (where 20wt% ≤ x ≤ 70wt%; 10wt% ≤ y ≤ 60wt%; 0wt% ≤ z ≤ 40wt%). Alcohol is added at 5% - 15% during ball milling. Zirconia balls are used as the balls during ball milling, the diameter of the balls is XX - XXmm, the ball-to-material ratio is 1 - 3, and the ball milling time is 5 - 10 hours. A mixed powder with a particle size of 3 - 5nm of (SiO2) 1-x-y-z (Al2O3) x (CaO) y C z (where 20wt% ≤ x ≤ 70wt%; 10wt% ≤ y ≤ 60wt%; 0wt% ≤ z ≤ 40wt%) is obtained, and this application names it as the main component A.
[0009] Preparation of Zr-Ti-V metal compound getter material with added component B: ① Mix 99.9% pure Zr, Ti, and V elements according to a mass ratio of Zr 43.49Ti 2.54V 53.97wt%. ② Put the prepared raw materials into the copper crucible of the smelting furnace in the order of melting point from low to high, and then evacuate the smelting furnace to (1-5)×10 -3 Pa, then 99.9999% high-purity argon gas was introduced to clean the furnace, and then the vacuum was evacuated to (1-5)×10 -3 Pa. ③The alloy is then melted in an argon atmosphere of 0.05MPa. A CZL-300 vacuum magnetron tungsten arc furnace is used for melting. Turn on the power of the arc melting, first start the arc on the tungsten electrode, then stabilize the arc and melt on the titanium ingot. During melting, the melting current is about 80 to 220A. The Zr43.49Ti 2.54V 53.97 alloy is completely melted and cast into an ingot. In order to ensure the uniformity of the Ti 2.54V 53.97 alloy, the entire melting process needs to be melted 4 times. After each melting, the Ti 2.54V 53.97 alloy ingot is fully cooled, and then it is turned over by a robotic arm and melted again 4 times until it is uniform.
[0010] The smelted alloy is crushed and ball-milled under a protective Ar or N2 atmosphere. The pressure of the protective atmosphere is 0.04-0.2MPa and the ball-milling time is 2-10h. The powder is ball-milled to 270 mesh (50μm)-1800 mesh (8μm), 8-50 micron powder, to form the added component B.
[0011] The main component A and the added component B are physically mixed to form aAbB components to prepare a composite getter, wherein 60wt%≤a≤95wt%; 1wt%≤b≤40wt%.
[0012] The present invention has the following beneficial effects:
[0013] The getter material of the present invention not only greatly improves the absorption capacity of CO and H2O, but also enables the getter material to absorb N2 on the basis of absorbing CO and H2O. The problem of poor absorption capacity of N2 by existing metal oxides is improved, and the absorption capacity of metal oxide (SiO2) is improved. 1-x-y-z (Al2O3) x (CaO) y C z Capacity to absorb CO, H2O and N2. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 Schematic diagram of physical adsorption and chemical adsorption in the present invention. DETAILED DESCRIPTION
[0015] The terms "first", "second", "third", "fourth", etc. (if any) in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments described herein can be implemented in an order other than that illustrated or described herein. In addition, the terms "including" or "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.
[0016] For ease of understanding, the specific process of an embodiment of the present invention is described below. An embodiment of a composite getter material with high efficiency in absorbing nitrogen in an embodiment of the present invention includes:
[0017] A main component A and an additional component B, wherein the main component A and the additional component B form an aAbB composite getter, wherein a+b=100%; 50wt%≤a<100wt%; 0wt% <b<50wt%;
[0018] The main component A is composed of: (SiO2) 1-x-y-z (Al2O3) x (CaO) y C z , wherein 20wt%≤x≤70wt%; 10wt%≤y≤60wt%; 0wt%≤z≤40wt%; and the added component B is a metal compound Zr-Ti-V getter material.
[0019] As a preferred embodiment, the main component A is a powder with a particle size of 3-5 nm. As a preferred embodiment, the added component B is a powder with a particle size of 8-50 microns. As a preferred embodiment, in the aAbB composite getter, 60wt%≤a≤95wt%; 1wt%≤b≤40wt%.
[0020] A second aspect of the present invention provides a method for preparing a composite getter material having high efficiency in absorbing nitrogen, comprising the following steps:
[0021] SiO2, Al2O3, CaO and activated carbon C powders with different contents and powder particle sizes of 70-230 μm were prepared according to (SiO2) 1-x-y-z (Al2O3) x (CaO) y C zThe composition ratio (wherein 20wt%≤x≤70wt%; 10wt%≤y≤60wt%; 0wt%≤z≤40wt%) is put into a ball mill for ball milling, 5%-15% alcohol is added during ball milling, zirconium oxide balls are used during ball milling, the diameter of the balls is 0.1-300mm, the ball-to-material ratio is 1-3, and the ball milling time is 5-10 hours. The powder (SiO2) with a particle size of 3-5nm is obtained. 1-x-y-z (Al2O3) x (CaO) y C z (Wherein 20wt%≤x≤70wt%; 10wt%≤y≤60wt%; 0wt%≤z≤40wt%.) The mixed powder is named as main component A in this application.
[0022] Preparation of Zr-Ti-V metal compound getter material with added component B: ① Mix 99.9% pure Zr, Ti, and V elements according to a mass ratio of Zr 43.49Ti 2.54V 53.97wt%. ② Put the prepared raw materials into the copper crucible of the smelting furnace in the order of melting point from low to high, and then evacuate the smelting furnace to (1-5)×10 -3 Pa, then 99.9999% high-purity argon gas was introduced to clean the furnace, and then the vacuum was evacuated to (1-5)×10 -3 Pa. ③The alloy is then melted in an argon atmosphere of 0.05MPa. A CZL-300 vacuum magnetron tungsten arc furnace is used for melting. Turn on the power of the arc melting, first start the arc on the tungsten electrode, then stabilize the arc and melt on the titanium ingot. During melting, the melting current is about 80 to 220A. The Zr43.49Ti 2.54V 53.97 alloy is completely melted and cast into an ingot. In order to ensure the uniformity of the Ti 2.54V 53.97 alloy, the entire melting process needs to be melted 4 times. After each melting, the Ti 2.54V 53.97 alloy ingot is fully cooled, and then it is turned over by a robotic arm and melted again 4 times until it is uniform.
[0023] The smelted alloy is crushed and ball-milled under a protective Ar or N2 atmosphere, the pressure of the protective atmosphere is 0.04-0.2MPa, and the ball-milling time is 2-10h. The powder is ball-milled to 270-1800 mesh and 8-50 micron powder to form the added component B.
[0024] The main component A and the added component B are physically mixed to form aAbB components to prepare a composite getter, wherein 60wt%≤a≤95wt%; 1wt%≤b≤40wt%.
[0025] The present invention is based on the existing metal oxide getter (SiO2) 1-x-y-z (Al2O3) x (CaO) y C z (wherein 20wt%≤x≤70wt%; 10wt%≤y≤60wt%; 0wt%≤z≤40wt%.), these metal oxides SiO2, Al2O3, CaO, C are pressed into (SiO2) 1-x-y-z (Al2O3) x (CaO) y C z Mix in a certain proportion (wherein 20wt%≤x≤70wt%; 10wt%≤y≤60wt%; 0wt%≤z≤40wt%), and process by ball milling to obtain a powder with a particle size of 3-5nm. 1-x-y-z (Al2O3) x (CaO) y C z Named as main component A.
[0026] In the main component A with a size of 3-5nm, that is, in (SiO2) 1-x-y-z (Al2O3) x (CaO) y C z The metal compound Ti-Zr-V powder is added to the powder, and the added metal compound Ti-Zr-V powder is named as the added component B. The particle size of the added component B powder is 8-50 microns, forming a composite getter aAbB, a[(SiO2) 1-x-y-z (Al2O3) x (CaO) y C z ]b(TiZrV)(aAbB, wherein a+b=100%, 60wt%≤a≤95wt%; 1wt%≤b≤40wt%). The composite getter not only has the function of absorbing CO and H2O, but also has the function of absorbing N2.
[0027] like Figure 1 , in the main component A oxide (SiO2) 1-x-y-z (Al2O3) x (CaO) y C zWhen the added component B is added, the 3d electron orbits of Ti, Zr, and V in the compound powder interact with each other in the impurity gas CO gas, HO in the H2O gas, and NN in the N2 gas, so that the CO gas molecules, H2O gas molecules, and N2 gas molecules in the gas molecules change into C, H, and N atoms. Because for CO, H2O, and N2 gases, the atomic radius of C, H, and N is much smaller than the radius of gas molecules, it is precisely because the metal compound Ti-Zr-V getter has the function of dissociating gas molecules into small atomic radius C, H, and N, and because the small atomic radius can quickly move to the composite getter aAbB, a[(SiO2) 1-x-y-z (Al2O3) x (CaO) y C z ]b(TiZrV) diffuses, achieving the effect of increasing the air intake rate.
[0028] At the same time, when no metal compound is added, the adsorption force between the metal oxide and the gas molecules is only the van der Waals force, and the metal oxide cannot dissociate the hydrogen molecules in N2 into N atoms. However, when the metal compound Ti-Zr-V encounters N2, it is more effective to dissociate the N2 molecules into NN atoms. Therefore, when in the metal oxide (SiO2) 1-x-y-z (Al2O3) x (CaO) y C z After adding the metal compound Ti-Zr-V getter component B to the main component A, the aAbB composite getter a[(SiO2) 1-x-y-z (Al2O3) x (CaO) y C z ]b(TiZrV), the principle of gas absorption is not only the van der Waals force between gas molecules and composite getter, but also the adsorption effect of chemical bonds between atoms and composite getter, which greatly increases the absorption capacity of composite getter and also makes composite getter have the ability to absorb nitrogen.
[0029] The second aspect of the present invention provides a method for preparing a composite getter material with high efficiency in absorbing nitrogen, as shown in Examples 1 to 10:
[0030] Example 1, for an oxide getter with a main component A of 100% and an added component B of zero, the preparation steps are as follows:
[0031] 1) 55% SiO2 powder, 25% Al2O3 powder, 20% CaO powder and 5% activated carbon powder. The average particle size of the four powders is 72μm. Put them into a ball mill of model KF-4L for ball milling. The alcohol added during ball milling is 6%. The balls used during ball milling are zirconium oxide balls. The ball milling time is 5.5 hours. The average particle size of the powder is 3.8nm and the sample of Example 1 is obtained. (55% SiO220% Al2O320% CaO5% C) The specific surface area of the powder is 735m 2 / g. The sample has a true density of 5×10 - 4 Pa, activated at 500℃ for 20min, the ability to absorb CO gas at room temperature is 55ml / s.cm 2 , the nitrogen inhalation rate is 0. The specific composition ratio, powder particle size, and inhalation performance of Example 1 are shown in Table 1.
[0032] Example 2, wherein the main component A is 88% and the added component B is 12%, and the preparation steps are as follows:
[0033] 2) 55% SiO2 powder, 25% Al2O3 powder, 20% CaO powder and 5% activated carbon powder, the average particle size of the four powders is 75 μm, put them into a ball mill of model KF-4L for ball milling, 6.2% alcohol is added during ball milling, zirconium oxide balls are used during ball milling, the ball milling time is 8 hours, and the average particle size of the powder is 3.1 nm, thus obtaining component A.
[0034] 3) Preparation of the metal compound getter material with added components BZr-Ti-V: ① Prepare the Zr, Ti and V elements with a purity of 99.9% according to the formula of Zr 43.49Ti 2.54V 53.97wt%. ② Put the prepared raw materials into the copper crucible of the smelting furnace in the order of melting point from low to high, and then evacuate the smelting furnace to 2×10 -3 Pa, then 99.9999% high-purity argon gas was introduced to wash the furnace, and then the vacuum was evacuated to 2.3×10 -3Pa. ③ Then the alloy was melted in an argon atmosphere of 0.05MPa. A CZL-300 vacuum magnetron tungsten arc furnace was used for melting. Turn on the power of the arc melting, first start the arc on the tungsten electrode, and then stabilize the arc and melt on the titanium ingot. During melting, the melting current is about 90A. The Zr 43.49Ti2.54V53.97 alloy is completely melted and cast into an ingot. In order to ensure the uniformity of the Ti 2.54V 53.97 alloy, the entire melting process needs to be melted 4 times. After each melting, the Ti 2.54V 53.97 alloy ingot is fully cooled, and it is turned over by a mechanical arm and melted again 4 times until it is uniform. ④ The melted alloy is crushed and ball-milled for the Zr 43.49Ti 2.54V 53.97 alloy ingot under a protective Ar atmosphere. The pressure of the protective atmosphere is 0.08MPa and the ball-milling time is 3h. The powder is ball-milled to an average particle size of 30 μm to form an added component B powder.
[0035] 4) 88% of the main component A and 12% of the added component B were physically mixed to prepare a 88A12B composite powder getter, the specific surface area of the powder was 643m 2 / g, the vacuum degree of Example 2 is 4.9×10 -4 Pa, activated at 250℃ for 20min, the performance of absorbing CO gas at room temperature is 54ml / s.cm 2 , the nitrogen inhalation rate is 51ml / s.cm 2 By comparing Example 1 with Example 2, it can be seen that the addition of 12% of component B causes the 88A12B composite getter to absorb nitrogen instead of absorbing nitrogen. The specific composition ratio, powder particle size, and getter performance of Example 2 are shown in Table 1.
[0036] From the summary of Table 1, it can be found that when the metal oxide composition of the main component A is 55% SiO2 20% Al2O3 20% CaO 5% C (x = 20wt%; y = 20wt%; Z = 10wt%), if the metal compound Ti-Zr-V powder of the component B is not added, that is, 100% of the main component
[0037] A55%SiO220%Al2O320%CaO5%C. It can be seen that at room temperature, the rate of CO absorption by the gas is 55ml / s.cm 2 , the rate of absorbing N2 is 0.
[0038] When 12% of the additional component BTi-Zr-V getter is added to 55%SiO220%Al2O320%CaO5%C to form a composite [88%(55%SiO2·20%Al2O3·20%CaO·5%C)12%(TiZrV)] getter (88%A12%B), it can be seen that at room temperature, the composite 88%A12%B getter absorbs CO at a rate of 54ml / s.cm 2 , the rate of N2 absorption is 51ml / s.cm 2 , the addition of component B makes the getter 55% SiO220% Al2O320% CaO5% C that does not absorb N2 gas become a getter that absorbs N2 gas
[0039] [88%(55%SiO2·20%Al2O3·20%CaO·5%C)12%(TiZrV)].
[0040] The reason why the getter performance of 88%A12%B composite getter is increased by adding 12% of the metal compound Ti-Zr-V getter with added component B to 55%SiO2·20%Al2O3·20%CaO·5%C getter is: Figure 1 It can be seen that the added component B contains Ti, Zr, and V elements, among which the 3d electron orbits of these atoms have unpaired electrons, which have a strong dissociation effect on the impurity gas. It will break the CO bond of the CO gas molecule and dissociate it into C and O atoms. Similarly, it will break the HO bond in the H2O gas molecule and dissociate it into H and O atoms, and break the NN bond in the N2 gas and dissociate it into N atoms. The CO gas molecules, H2O gas molecules, and N2 gas molecules in the gas molecules are changed into C, H, and O atoms.
[0041] Because for gas molecules, the atomic radius is much smaller than the gas molecule radius, the gas atoms quickly diffuse into the composite getter to form 88A12B composite getter, thereby increasing the gettering rate.
[0042] Example 3, wherein the main component A is 88% and the added component B is 12%, and the preparation steps are as follows:
[0043] 1) 55% SiO2 powder, 25% Al2O3 powder, 20% CaO powder and 5% activated carbon powder, the average particle size of the four powders being 80 μm, are put into a ball mill of model KF-4L for ball milling, 6.5% alcohol is added during ball milling, zirconium oxide balls are used during ball milling, and the ball milling time is 5.9 hours to obtain a powder with an average particle size of 4.0 nm, thereby obtaining component A.
[0044] 2) Preparation of the metal compound getter material with added components BZr-Ti-V: ① The Zr, Ti, and V elements with a purity of 99.9% are prepared according to a formula of Zr 43.49Ti 2.54V 53.97wt%. ② The prepared raw materials are placed in the copper crucible of the smelting furnace in the order of melting point from low to high, and then the smelting furnace is evacuated to 3×10 -3 Pa, then 99.9999% high-purity argon was introduced to wash the furnace, and then the vacuum was evacuated to 3×10 -3 Pa. ③The alloy is then melted in an argon atmosphere of 0.05MPa. A CZL-300 vacuum magnetron tungsten arc furnace is used for melting. Turn on the power of the arc melting, first start the arc on the tungsten electrode, then stabilize the arc and melt on the titanium ingot. During melting, the melting current is about 100A. The Zr 43.49Ti2.54V 53.97 alloy is completely melted and cast into an ingot. In order to ensure the uniformity of the Ti 2.54V 53.97 alloy, the entire melting process needs to be melted 4 times. After each melting, the Ti 2.54V 53.97 alloy ingot is fully cooled, and then it is turned over by a robotic arm and melted again 4 times until it is uniform. ④ The smelted alloy was crushed and ball-milled under a protective Ar atmosphere. The pressure of the protective atmosphere was 0.09 MPa and the ball-milling time was 3.5 h. The powder was ball-milled to an average particle size of 32 μm to form an added component B powder.
[0045] 3) 99% of the main component A and 1% of the added component B were physically mixed to prepare a 99A1B composite powder getter with a specific surface area of 715m 2 / g, the vacuum degree of Example 3 is 5.0×10 -4 Pa, activated at 500℃ for 20min, the performance of absorbing CO gas at room temperature is 53ml / s.cm 2 , the nitrogen inhalation rate is 5ml / s.cm 2 By comparing Example 1 with Example 3, it can be seen that due to the addition of 1% of the additive component B, the composite getter changes from not absorbing nitrogen to absorbing nitrogen. The specific component ratio, powder particle size, and getter performance of Example 3 are shown in Table 1.
[0046] Example 4, wherein the main component A is 96% and the added component B is 4%, and the preparation steps are as follows:
[0047] 1) 55% SiO2 powder, 25% Al2O3 powder, 20% CaO powder and 5% activated carbon powder. The average particle size of the four powders is 85 μm. Put them into a ball mill of model KF-4L for ball milling. The alcohol added during ball milling is 7%. The balls used during ball milling are zirconium oxide balls. The ball milling time is 6.5 hours. The average particle size of the powder is 4.2 nm, and component A is obtained.
[0048] 2) Preparation of the metal compound getter material with added components BZr-Ti-V: ① The Zr, Ti and V elements with a purity of 99.9% are prepared according to a formula of Zr 43.49Ti 2.54V 53.97wt%. ② The prepared raw materials are placed in the copper crucible of the smelting furnace in the order of melting point from low to high, and then the smelting furnace is evacuated to 3.2×10 -3 Pa, then 99.9999% high-purity argon was introduced to wash the furnace, and then the vacuum was evacuated to 3.5×10 -3 Pa. ③The alloy is then melted in an argon atmosphere of 0.05MPa. A CZL-300 vacuum magnetron tungsten arc furnace is used for melting. Turn on the power of the arc melting, first start the arc on the tungsten electrode, then stabilize the arc and melt on the titanium ingot. During melting, the melting current is about 110A. The Zr 43.49Ti2.54V53.97 alloy is completely melted and cast into an ingot. In order to ensure the uniformity of the Ti 2.54V 53.97 alloy, the entire melting process needs to be melted 4 times. After each melting, the Ti 2.54V 53.97 alloy ingot is fully cooled, and then it is turned over by a robotic arm and melted again 4 times until it is uniform. ④ The smelted alloy was crushed and ball-milled under a protective Ar atmosphere. The pressure of the protective atmosphere was 0.10 MPa and the ball-milling time was 4 hours. The powder was ball-milled to an average particle size of 31 μm to form a powder of the added component B.
[0049] 3) 96% of the main component A and 4% of the added component B were physically mixed to prepare a 99A1B composite powder getter with a specific surface area of 723 m 2 / g, the vacuum degree of Example 4 is 5.0×10 -4 Pa, activated at 500℃ for 20min, the performance of absorbing CO gas at room temperature is 51ml / s.cm 2 , the nitrogen inhalation rate is 15ml / s.cm 2 By comparing Example 1 with Example 4, it can be seen that due to the addition of 4% of the additive component B, the composite getter changes from not absorbing nitrogen to absorbing nitrogen. The specific component ratio, powder particle size, and getter performance of Example 4 are shown in Table 1.
[0050] Example 5, wherein the main component A is 92% and the added component B is 8%, and the preparation steps are as follows:
[0051] 1) 55% SiO2 powder, 25% Al2O3 powder, 20% CaO powder and 5% activated carbon powder. The average particle size of the four powders is 88 μm. Put them into a ball mill of model KF-4L for ball milling. The alcohol added during ball milling is 7.7%. The balls used during ball milling are zirconium oxide balls. The ball milling time is 6.5 hours. The average particle size of the powder is 4.3 nm, and component A is obtained.
[0052] 2) Preparation of the metal compound getter material with added components BZr-Ti-V: ① The Zr, Ti, and V elements with a purity of 99.9% are prepared according to a formula of Zr 43.49Ti 2.54V 53.97wt%. ② The prepared raw materials are placed in the copper crucible of the smelting furnace in the order of melting point from low to high, and then the smelting furnace is evacuated to 3.5×10 -3 Pa, then 99.9999% high-purity argon gas was introduced to wash the furnace, and then the vacuum was evacuated to 3.7×10 -3 Pa. ③The alloy is then melted in an argon atmosphere of 0.05MPa. A CZL-300 vacuum magnetron tungsten arc furnace is used for melting. Turn on the power of the arc melting, first start the arc on the tungsten electrode, then stabilize the arc and melt on the titanium ingot. During melting, the melting current is about 123A. The Zr 43.49Ti2.54V 53.97 alloy is completely melted and cast into an ingot. In order to ensure the uniformity of the Ti 2.54V 53.97 alloy, the entire melting process needs to be melted 4 times. After each melting, the Ti 2.54V 53.97 alloy ingot is fully cooled, and then it is turned over by a robotic arm and melted again 4 times until it is uniform. ④ The smelted alloy was crushed and ball-milled under a protective Ar atmosphere. The pressure of the protective atmosphere was 0.11 MPa and the ball-milling time was 4.2 h. The powder was ball-milled to an average particle size of 33 μm to form an added component B powder.
[0053] 3) 96% of the main component A and 4% of the added component B were physically mixed to prepare a 92A8B composite powder getter, the specific surface area of the powder was 706m 2 / g, the vacuum degree of Example 4 is 5.0×10 -4 Pa, activated at 500℃ for 20min, the performance of absorbing CO gas at room temperature is 52ml / s.cm 2 , the nitrogen inhalation rate is 31ml / s.cm 2By comparing Example 1 with Example 5, it can be seen that due to the addition of 8% of the additive component B, the composite getter changes from not absorbing nitrogen to absorbing nitrogen. The specific component ratio, powder particle size, and getter performance of Example 5 are shown in Table 1.
[0054] Example 6, wherein the main component A is 84% and the added component B is 16%, and the preparation steps are as follows:
[0055] 1) 55% SiO2 powder, 25% Al2O3 powder, 20% CaO powder and 5% activated carbon powder, the average particle size of the four powders is 90 μm, put them into a ball mill of model KF-4L for ball milling, 7.9% alcohol is added during ball milling, zirconium oxide balls are used during ball milling, the ball milling time is 6.5 hours, and the average particle size of the powder is 4.5 nm, thus obtaining component A.
[0056] 2) Preparation of the metal compound getter material with added components BZr-Ti-V: ① The Zr, Ti, and V elements with a purity of 99.9% are prepared according to a formula of Zr 43.49Ti 2.54V 53.97wt%. ② The prepared raw materials are placed in the copper crucible of the smelting furnace in the order of melting point from low to high, and then the smelting furnace is evacuated to 3.5×10 -3 Pa, then 99.9999% high-purity argon gas was introduced to wash the furnace, and then the vacuum was evacuated to 3.7×10 -3 Pa. ③The alloy was then melted in an argon atmosphere of 0.05MPa. A CZL-300 vacuum magnetron tungsten arc furnace was used for melting. Turn on the power of the arc melting, first start the arc on the tungsten electrode, then stabilize the arc and melt on the titanium ingot. During melting, the melting current is about 131A. The Zr 43.49Ti2.54V 53.97 alloy is completely melted and cast into an ingot. In order to ensure the uniformity of the Ti 2.54V 53.97 alloy, the entire melting process needs to be melted 4 times. After each melting, the Ti 2.54V 53.97 alloy ingot is fully cooled, and then it is turned over by a robotic arm and melted again 4 times until it is uniform. ④ The smelted alloy was crushed and ball-milled under a protective Ar atmosphere. The pressure of the protective atmosphere was 0.13 MPa and the ball-milling time was 4.2 h. The powder was ball-milled to an average particle size of 34 μm to form an added component B powder.
[0057] 3) 84% of the main component A and 16% of the added component B were physically mixed to prepare a 92A8B composite powder getter with a specific surface area of 672 m 2 / g, the vacuum degree of Example 4 is 5.0×10 -4Pa, activated at 500℃ for 20min, the performance of absorbing CO gas at room temperature is 45ml / s.cm 2 , the nitrogen inhalation rate is 67ml / s.cm 2 By comparing Example 1 with Example 6, it can be seen that due to the addition of 16% of component B, the composite getter changes from not absorbing nitrogen to absorbing nitrogen. The specific component ratio, powder particle size, and getter performance of Example 6 are shown in Table 1.
[0058] Example 7, wherein the main component A is 80% and the added component B is 20%, and the preparation steps are as follows:
[0059] 1) 55% SiO2 powder, 25% Al2O3 powder, 20% CaO powder and 5% activated carbon powder. The average particle size of the four powders is 92 μm. Put them into a ball mill of model KF-4L for ball milling. The alcohol added during ball milling is 8.3%. The balls used during ball milling are zirconium oxide balls. The ball milling time is 8 hours. The average particle size of the powder is 4.4 nm, and component A is obtained.
[0060] 2) Preparation of the metal compound getter material with added components BZr-Ti-V: ① The Zr, Ti, and V elements with a purity of 99.9% are prepared according to a formula of Zr 43.49Ti 2.54V 53.97wt%. ② The prepared raw materials are placed in the copper crucible of the smelting furnace in the order of melting point from low to high, and then the smelting furnace is evacuated to 3.6×10 -3 Pa, then 99.9999% high-purity argon gas was introduced to clean the furnace, and then the vacuum was evacuated to 4×10 -3 Pa. ③The alloy is then melted in an argon atmosphere of 0.05MPa. A CZL-300 vacuum magnetron tungsten arc furnace is used for melting. Turn on the power of the arc melting, first start the arc on the tungsten electrode, then stabilize the arc and melt on the titanium ingot. During melting, the melting current is about 138A. The Zr 43.49Ti2.54V 53.97 alloy is completely melted and cast into an ingot. In order to ensure the uniformity of the Ti 2.54V 53.97 alloy, the entire melting process needs to be melted 4 times. After each melting, the Ti 2.54V 53.97 alloy ingot is fully cooled, and then it is turned over by a robotic arm and melted again 4 times until it is uniform. ④ The smelted alloy was crushed and ball-milled under a protective Ar atmosphere. The pressure of the protective atmosphere was 0.14 MPa and the ball-milling time was 4.0 h. The powder was ball-milled to an average particle size of 37 μm to form an added component B powder.
[0061] 3) 84% of the main component A and 16% of the added component B were physically mixed to prepare a 92A8B composite powder getter with a specific surface area of 658 m 2 / g, the vacuum degree of Example 4 is 5.0×10 -4 Pa, activated at 500℃ for 20min, the performance of absorbing CO gas at room temperature is 43ml / s.cm 2 , the nitrogen inhalation rate is 69ml / s.cm 2 By comparing Example 1 with Example 7, it can be seen that the composite getter changes from not absorbing nitrogen to absorbing nitrogen due to the addition of 16% of component B. The specific composition ratio, powder particle size, and getter performance of Example 7 are shown in Table 1.
[0062] Example 8, wherein the main component A is 76% and the added component B is 24%, and the preparation steps are as follows:
[0063] 1) 55% SiO2 powder, 25% Al2O3 powder, 20% CaO powder and 5% activated carbon powder. The average particle size of the four powders is 90 μm. Put them into a ball mill of model KF-4L for ball milling. The alcohol added during ball milling is 8.1%. The balls used during ball milling are zirconium oxide balls. The ball milling time is 7.8 hours. The average particle size of the powder is 4.3 nm, and component A is obtained.
[0064] 2) Preparation of Zr-Ti-V metal compound getter material with added component B: ① Prepare Zr, Ti and V elements with a purity of 99.9% according to a formula of Zr 43.49Ti 2.54V 53.97wt%. ② Put the prepared raw materials into the copper crucible of the smelting furnace in the order of melting point from low to high, and then evacuate the smelting furnace to 3.6×10 -3 Pa, then 99.9999% high-purity argon gas was introduced to clean the furnace, and then the vacuum was evacuated to 4×10 -3Pa. ③The alloy is then melted in an argon atmosphere of 0.05MPa. A CZL-300 vacuum magnetron tungsten arc furnace is used for melting. Turn on the power of the arc melting, first start the arc on the tungsten electrode, then stabilize the arc and melt on the titanium ingot. During melting, the melting current is about 140A. The Zr 43.49Ti2.54V 53.97 alloy is completely melted and cast into an ingot. In order to ensure the uniformity of the Ti 2.54V 53.97 alloy, the entire melting process needs to be melted 4 times. After each melting, the Ti 2.54V 53.97 alloy ingot is fully cooled, and then it is turned over by a robotic arm and melted again 4 times until it is uniform. ④ The smelted alloy was crushed and ball-milled under a protective Ar atmosphere. The pressure of the protective atmosphere was 0.14 MPa and the ball-milling time was 3.9 h. The powder was ball-milled to an average particle size of 38 μm to form a powder of the added component B.
[0065] 3) 76% of the main component A and 24% of the added component B were physically mixed to prepare a 92A8B composite powder getter with a specific surface area of 643 m 2 / g, the vacuum degree of Example 4 is 5.0×10 -4 Pa, activated at 250℃ for 20min, the performance of absorbing CO gas at room temperature is 40ml / s.cm 2 , the nitrogen inhalation rate is 71ml / s.cm 2 By comparing Example 1 with Example 8, it can be seen that due to the addition of 16% of the additive component B, the composite getter changes from not absorbing nitrogen to absorbing nitrogen. The specific component ratio, powder particle size, and getter performance of Example 7 are shown in Table 1.
[0066] Example 9, wherein the main component A is 88% and the added component B is 12%, and the preparation steps are as follows:
[0067] 1) 55% SiO2 powder, 25% Al2O3 powder, 20% CaO powder and 5% activated carbon powder, the average particle size of the four powders being 90 μm, were put into a ball mill of model KF-4L for ball milling, 8.1% alcohol was added during ball milling, zirconium oxide balls were used during ball milling, and the ball milling time was 7.1 hours to obtain a powder with an average particle size of 4.5 nm, thus obtaining component A.
[0068] 2) Preparation of Zr-Ti-V metal compound getter material with added component B: ① Prepare Zr, Ti and V elements with a purity of 99.9% according to a formula of Zr 43.49Ti 2.54V 53.97wt%. ② Put the prepared raw materials into the copper crucible of the smelting furnace in the order of melting point from low to high, and then evacuate the smelting furnace to 3.6×10-3 Pa, then 99.9999% high-purity argon gas was introduced to clean the furnace, and then the vacuum was evacuated to 4×10 -3 Pa. ③The alloy is then melted in an argon atmosphere of 0.05MPa. A CZL-300 vacuum magnetron tungsten arc furnace is used for melting. Turn on the power of the arc melting, first start the arc on the tungsten electrode, then stabilize the arc and melt on the titanium ingot. During melting, the melting current is about 140A. The Zr 43.49Ti2.54V 53.97 alloy is completely melted and cast into an ingot. In order to ensure the uniformity of the Ti 2.54V 53.97 alloy, the entire melting process needs to be melted 4 times. After each melting, the Ti 2.54V 53.97 alloy ingot is fully cooled, and then it is turned over by a robotic arm and melted again 4 times until it is uniform. ④ The smelted alloy was crushed and ball-milled under a protective Ar atmosphere. The pressure of the protective atmosphere was 0.14 MPa and the ball-milling time was 4 h. The powder was ball-milled to an average particle size of 35 μm to form a powder of the added component B.
[0069] 3) 76% of the main component A and 24% of the added component B were physically mixed to prepare a 92A8B composite powder getter with a specific surface area of 643 m 2 / g, the vacuum degree of Example 4 is 5.0×10 -4 Pa, activated at 250℃ for 20min, the performance of absorbing CO gas at room temperature is 40ml / s.cm 2 , the nitrogen inhalation rate is 71ml / s.cm 2 By comparing Example 1 with Example 8, it can be seen that due to the addition of 16% of the additive component B, the composite getter changes from not absorbing nitrogen to absorbing nitrogen. The specific component ratio, powder particle size, and getter performance of Example 7 are shown in Table 1.
[0070] Example 10, wherein the main component A is 88% and the added component B is 12%, and the preparation steps are as follows:
[0071] 1) 55% SiO2 powder, 25% Al2O3 powder, 20% CaO powder and 5% activated carbon powder, the average particle size of the four powders is 90 μm, put them into a ball mill of model KF-4L for ball milling, 8.1% alcohol is added during ball milling, zirconium oxide balls are used during ball milling, the ball milling time is 6.3 hours, and the average particle size of the powder is 5.8 nm, thus obtaining component A.
[0072] 2) Preparation of Zr-Ti-V metal compound getter material with added component B: ① Prepare Zr, Ti and V elements with a purity of 99.9% according to a formula of Zr 43.49Ti 2.54V 53.97wt%. ② Put the prepared raw materials into the copper crucible of the smelting furnace in the order of melting point from low to high, and then evacuate the smelting furnace to 3.6×10 -3 Pa, then 99.9999% high-purity argon gas was introduced to clean the furnace, and then the vacuum was evacuated to 4×10 -3 Pa. ③The alloy is then melted in an argon atmosphere of 0.05MPa. A CZL-300 vacuum magnetron tungsten arc furnace is used for melting. Turn on the power of the arc melting, first start the arc on the tungsten electrode, then stabilize the arc and melt on the titanium ingot. During melting, the melting current is about 140A. The Zr 43.49Ti2.54V 53.97 alloy is completely melted and cast into an ingot. In order to ensure the uniformity of the Ti 2.54V 53.97 alloy, the entire melting process needs to be melted 4 times. After each melting, the Ti 2.54V 53.97 alloy ingot is fully cooled, and then it is turned over by a robotic arm and melted again 4 times until it is uniform. ④ The smelted alloy was crushed and ball-milled under a protective Ar atmosphere. The pressure of the protective atmosphere was 0.14 MPa and the ball-milling time was 3.5 h. The powder was ball-milled to an average particle size of 43 μm to form an added component B powder.
[0073] 3) 76% of the main component A and 24% of the added component B were physically mixed to prepare a 92A8B composite powder getter with a specific surface area of 643 m 2 / g, the vacuum degree of Example 4 is 5.0×10 -4 Pa, activated at 250℃ for 20min, the performance of absorbing CO gas at room temperature is 40ml / s.cm 2 , the nitrogen inhalation rate is 71ml / s.cm 2 By comparing Example 1 with Example 8, it can be seen that due to the addition of 16% of the additive component B, the composite getter changes from not absorbing nitrogen to absorbing nitrogen. The specific component ratio, powder particle size, and getter performance of Example 7 are shown in Table 1.
[0074] Table 1
[0075]
[0076]
[0077] It can be seen from Table 1 that in (SiO2) 1-x-y-z (Al2O3) x (CaO)y C z In the getter, when x=25wt%, y=20wt%, Z=5wt%, b=0wt%, 1wt%, 4wt%, 8wt%, 12wt%, 16wt%, 24wt% of the added component B getter are added to (55% SiO2·25% Al2O3·20% CaO·5% C) to form composite getters 99A1B, 96A4B, 92A8B, 88A12B, 84A16B, 80A20B. These composite getters have the ability to absorb N2 on the basis of absorbing CO at room temperature. The absorption capacity of CO and N2 is 55ml / s.cm 2 , 0 (A getter, not a composite getter); 53ml / s.cm 2 、5ml / s.cm 2 (99A1B composite getter); 51ml / s.cm 2 、15ml / s.cm 2 (96A4B composite getter); 52ml / s.cm 2 、31ml / s.cm 2 (92A8B composite getter); 54ml / s.cm 2 、51ml / s.cm 2 (88A12B composite getter); 45ml / s.cm 2 、67ml / s.cm 2 (84A16B composite getter); 43ml / s.cm 2 、69ml / s.cm 2 (80A20B composite getter). It can be seen that with the addition of component B, the ability to absorb N2 is gradually enhanced. When the B content is greater than 16%, the N2 adsorption performance is limited, but the CO performance has a downward trend. When the content of added component B is in the range of 12%-16%, the composite getter aAbB has the best absorption performance.
[0078] At the same time, it can be seen from Table 1 that, under the same B component content, the smaller the powder particle size, the larger the specific surface area, and the stronger the air absorption capacity. For example, by comparing Example 2 with Example 9 and Example 10, it can be seen that for the same 88A12B composite getter, by comparing the average powder particle size of component A and component B in Example 2 with Example 9 and Example 10, it can be seen that as the powder particle size of these composite getters decreases, the ability to absorb CO and N2 at room temperature increases. As the powder particle size decreases, its ability to absorb CO and N2 increases from 47ml / s.cm 2 、43ml / s.cm 2(A and B particle sizes are 5.8nm and 43μm respectively) increased to 54ml / s.cm 2 、51ml / s.cm 2 (The particle sizes of A and B are 3.1nm and 30μm respectively), so when the A component is 3-4nm and the B component is 30-35um, the composite getter aAbB has the best gettering performance.
[0079] In short, in the main component A (SiO2) 1-x-y-z (Al2O3) x (CaO) y C z On this basis, the additional component B is added. At the same time, due to the refinement of the powder particle size of the main component A and the additional component B, the coupling effect of the combination of the two getters is obvious, so that the composite getter has the ability to absorb N2 on the basis of absorbing CO.
[0080] As described above, the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A composite getter material for absorbing nitrogen, characterized in that: The composite getter material comprises a main component A and an additional component B, wherein the main component A and the additional component B form an aAbB composite getter, wherein a+b=100%; 50wt%≤a<100wt%; 0wt% <b<50wt%; The components of the main component A are: (SiO2) 1-x-y-z (Al2O3) x (CaO) y C z Among them, 20wt%≤x≤70wt%;10wt%≤y≤60wt%;0wt%≤z≤40wt%; The added component B is a metal compound Zr-Ti-V getter material; The preparation method of the main component A is: SiO2, Al2O3, CaO and activated carbon C powders are put into a ball mill according to the composition ratio for ball milling. 5-15wt% alcohol is added during ball milling. The balls used for ball milling are zirconia balls with a ball diameter of 5-300mm. The ball-to-material ratio is 1-3. The ball milling time is 5-10 hours to obtain a main component A mixed powder with a powder particle size of 3-5nm.
2. A composite getter material for absorbing nitrogen according to claim 1, characterized in that: The main component A is a powder with a particle size of 3-5 nm.
3. A composite getter material for absorbing nitrogen according to claim 1, characterized in that: The added component B is a powder with a particle size of 8-50 microns.
4. A composite getter material for absorbing nitrogen according to claim 1, characterized in that: In the aAbB composite getter, 60wt%≤a≤95wt%; 1wt%≤b≤40wt%.
5. A composite getter material for absorbing nitrogen according to claim 1, characterized in that: The preparation method of the added component B is: The Zr, Ti and V elements with a purity of 99.9% are mixed according to the mass ratio; Put the prepared raw materials into the copper crucible of the smelting furnace in the order of melting point from low to high, and then evacuate the smelting furnace to 1-5×10 -3 Pa, then 99.9999% high-purity argon gas was introduced to clean the furnace, and then the vacuum was evacuated to 1-5×10 -3 Pa; Then, the alloy is melted in an argon atmosphere of 0.05 MPa, and a vacuum magnetron tungsten arc furnace is used for melting. The arc melting power is turned on, and the arc is first started on the tungsten electrode, and then the arc is stabilized and melted on the titanium ingot. During melting, the melting current is 80-220 A, so that the alloy is completely melted and cast into an ingot. The whole melting process needs to be melted 4 times. After each melting, the Ti V alloy ingot is fully cooled, and it is turned over by a mechanical arm and melted again 4 times until it is uniform. The smelted alloy is crushed and ball-milled under a protective atmosphere. The pressure of the protective atmosphere is 0.04-0.2 MPa and the ball-milling time is 2-10 hours. The powder is ball-milled to 270-1800 mesh and 8-50 micron powder to obtain the added component B.
6. A method for preparing a composite getter material for absorbing nitrogen, characterized in that: The following steps are involved: SiO2, Al2O3, CaO and activated carbon C powders are put into a ball mill according to the composition ratio for ball milling, 5-15wt% alcohol is added during ball milling, the ball used for ball milling is zirconia ball, the ball diameter is 5-300mm, the ball-to-material ratio is 1-3, the ball milling time is 5-10 hours, and the main component A mixed powder with a powder particle size of 3-5nm is obtained; The Zr, Ti and V elements with a purity of 99.9% are mixed according to the mass ratio; Put the prepared raw materials into the copper crucible of the smelting furnace in the order of melting point from low to high, and then evacuate the smelting furnace to 1-5×10 -3 Pa, then 99.9999% high-purity argon gas was introduced to clean the furnace, and then the vacuum was evacuated to 1-5×10 -3 Pa; Then, the alloy is melted in an argon atmosphere of 0.05 MPa, and a vacuum magnetron tungsten arc furnace is used for melting. The arc melting power is turned on, and the arc is first started on the tungsten electrode, and then the arc is stabilized and melted on the titanium ingot. During melting, the melting current is 80-220 A, so that the alloy is completely melted and cast into an ingot. The whole melting process needs to be melted 4 times. After each melting, the Ti V alloy ingot is fully cooled, and it is turned over by a mechanical arm and melted again 4 times until it is uniform. The smelted alloy is crushed and ball-milled under a protective atmosphere, the pressure of the protective atmosphere is 0.04-0.2 MPa, and the ball-milling time is 2-10 hours; the powder is ball-milled to 270-1800 mesh, 8-50 micron powder, to obtain the added component B; The main component A and the added component B are physically mixed to form aAbB components.
Citation Information
Patent Citations
Calcium oxide-based high-temperature CO2 adsorbent and its preparation method
CN107376826A
Cited By
Getter capable of efficiently absorbing CO, O2, H2, H2O and N2 and preparation method of getter
CN120001327A